Development of an SPR-Based biosensor applicable to the rapid and early detection of disease biomarkers - Peerawich Sukcharoenchaikul; Ricco, Raffaele; Trau, Dieter Wilhelm; Bora, Tanujjal; Royal Thai Government Fellowship (Pathum Thani : Asian Institute of Technology, 2022)
From centuries, infectious diseases have been one of the main factors influencing human{u2019}s mortality rate, thus disease{u2019}s detection is crucial to keep it low. It has been proved that early detection of diseases can potentially ease the severity and increases precise diagnosis for proper treatment. This research will be focused on stimulating biosensor usage by applying an optical biosensor in detecting glycated albumin which is a mockup of a biomarker. By using an optical biosensor applied with surface plasmon resonance (SPR) in detecting glycated albumin in order to analyze SPR peak shift of gold particles that deposit on ZnO nanorods which have aptamers immobilization on the gold surface. In this research, the biosensor has been used to evaluate glycated albumin at several concentrations and it has been found that the glycated albumin could be rapidly analyzed that the biosensor can detect. In future implications, this research could be potentially further developed to be used with a biomarker that is a real infectious disease to increase the disease{u2019}s detection preciseness and speediness.
Thesis (M. Eng.) - Asian Institute of Technology, 2022
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Nanotechnology
Keywords: Surface plasmon resonance; Biosensors